2013
DOI: 10.34101/actaagrar/53/2120
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in somereproductive parameters of Dorper Rams in Hungary

Abstract: The purpose of the present study was to test the hypothesis that season has an affect on semen quality and scrotal circumference of Dorper rams. The experiment was carried out with six Dorper rams aged between 15 and 18 month. Semen samples were collected with artificial vagina and volume, concentration (x 109/ml), total sperm number/ejaculate (x 109), mass motility (0–5), progressive motility (%), scrotal circumference (cm) was observed. Significant differences (P<0.05) were observed in concentration, tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The results of the current study showed that the season had a clear effect (p≤0.05) on the measurement of the scrotal circumference (Fig. 1), the highest rate recorded in the autumn and winter, while the lowest recorded in the summer and spring, similar observations were published by (10) in Dorper rams, (11) in Iranian Karakul rams, (17) in Awassi rams and (20) in Texel, Suffolk and Ile-de-France rams, in another study (21) the highest measure of the scrotum circumference in Brazilian Suffolk rams was recorded in spring and summer, This difference could be linked to the effect of climate and region (4).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The results of the current study showed that the season had a clear effect (p≤0.05) on the measurement of the scrotal circumference (Fig. 1), the highest rate recorded in the autumn and winter, while the lowest recorded in the summer and spring, similar observations were published by (10) in Dorper rams, (11) in Iranian Karakul rams, (17) in Awassi rams and (20) in Texel, Suffolk and Ile-de-France rams, in another study (21) the highest measure of the scrotum circumference in Brazilian Suffolk rams was recorded in spring and summer, This difference could be linked to the effect of climate and region (4).…”
Section: Resultssupporting
confidence: 88%
“…It has close relation to the concentration of sperm production from the testes (9). The season has a significant effect on the size of the testicles as the lack of daylight increases spermatogenesis and increases the circumference of the scrotum (10). As the largest diameter of the scrotal circumference can reach it in the fall and decrease by 2-3 cm in spring 7, so, the difference in testicular size during the annual breeding cycle of rams can be used as a measure of the degree of seasonal variation in different breeds (2).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Due to its outstanding characteristics, such as the thermotolerance ability (Joy et al 2020 ), the Dorper has gained popularity in certain European regions, including Hungary (Gavojdian et al 2013 ). Since its introduction in 2007, the Dorper has been one of the most prolific breeds found in Hungary (Budai et al 2013 ), although the number of purebreds in Hungary is still limited, and the ram is mainly used as terminal sires for crossbreeding with indigenous maternal breeds to increase production traits (Gavojdian et al 2015a , b ). According to some authors, the drawback of this breed to European rearing conditions would be the lower resistance to diseases, as evidenced by previous findings by Guo et al ( 2016 ) and Estrada-Reyes et al ( 2019 ).…”
Section: Discussionmentioning
confidence: 99%